High efficiency solid-state sensitized solar cell-based on submicrometer rutile TiO2 nanorod and CH3NH3PbI3 perovskite sensitizer - Kulkarni, Sneha A. (2013)
We report a highly efficient solar cell based on a submicrometer (0.6 μm) rutile TiO2 nanorod sensitized with CH3NH3PbI3 perovskite nanodots. Rutile nanorods were grown hydrothermally and their lengths were varied through the control of the reaction time. Infiltration of spiro-MeOTAD hole transport material into the perovskite-sensitized nanorod films demonstrated photocurrent density of 15.6 mA/cm2, voltage of 955 mV, and fill factor of 0.63, leading to a power conversion efficiency (PCE) of 9.4% under the simulated AM 1.5G one sun illumination. Photovoltaic performance was significantly dependent on the length of the nanorods, where both photocurrent and voltage decreased with increasing nanorod lengths. A continuous drop of voltage with increasing nanorod length correlated with charge generation efficiency rather than recombination kinetics with impedance spectroscopic characterization displaying similar recombination regardless of the nanorod length.